Development of a comprehensive method for analyzing clerodane-type diterpenes and phenolic compounds from Casearia sylvestris Swartz (Salicaceae) based on ultra high performance liquid chromatography combined with chemometric tools - Pires Bueno, Paula Carolina [UNESP]; Verbi Pereira, Fabiola Manhas [UNESP]; Torres, Roseli Buzanelli; Cavalheiro, Alberto Jose [UNESP] (Wiley-Blackwell, 2015)
This work describes the development and optimization of an analytical method utilizing liquid chromatography and chemometrics to evaluate and differentiate two varieties of Casearia sylvestris Swartz (Salicaceae) from São Paulo State (Brazil) based on their secondary metabolite profiles. Previously, analytical studies only concerned the analysis of clerodane-type diterpenes. Therefore, considering the importance of including phenolic compounds in such analysis, we used design of experiments to simultaneously extract and detect the largest number of compounds from both chemical classes. This new strategy allowed a comprehensive chromatographic analysis of C. sylvestris, and the results for the two varieties exhibited an interesting distribution according to their original ecosystems, suggesting a strong correlation to the main metabolites found in each species group. Besides their inherent morphological differences, C. sylvestris variety lingua, mainly found in Cerrado areas, predominantly contains phenolic compounds, while C. sylvestris variety sylvestris, mainly found in Atlantic Forest areas, contains mostly clerodane-type diterpenes. Finally, it was also possible to observe differences in the secondary metabolite composition within each group depending on the place where samples were collected.
Keywords: Casearia sylvestris; Chemical variability; Chemometrics; Metabolites